Harry Potter and the prisoner of Azkaban [videorecording (DVD)] - Cuarón, Alfonso; Radcliffe, Daniel, 1989-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Rowling, J. K. (Distributed by Warner Home Video, 2007)
Year three at Hogwarts means new fun and challenges as Harry learns the delicate art of approaching a Hippogriff, transforming shape-shifting Boggarts into hilarity and even turning back time. But the term also brings danger: soul-sucking Dementors hover over the school, an ally of the accursed He-Who-Cannot-Be-Named lurks within the castle walls, and fearsome wizard Sirius Black escapes Azkaban.